TEACHERS’ VIEW ON THE USE OF ICT IN ENGLISH PHARMACY COURSE - Rosmayanti, Vivit; Wahid, Areski; Mansur, Musdalifah; Hardianti, Hardianti; Asrifan, Andi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study investigates teachers’ perception on the use of ICT in ESP class. This research employed a qualitative case study. The semi structured interview was used to collect the data. The data from the interview were analyzed with Thematic Analysis using Nvivo R14 software. The qualitative data analysis resulted in two primary themes supported with several subthemes. The two primary themes are teachers’ positive perception and teachers’ challenges. The teachers perceived ICT facilitates ESP teaching and it makes teaching more enjoyable. However, the challenges such as the increase of copy-paste/cheating habits, limited internet access and the difficulty of monitoring students still occur during the class. The findings of this study would give a better insight of what constitutes an environment that is conducive for learning where ICT is integrated into the classroom especially ESP class.